Super-refractory status epilepticus in a woman with Aeromonas caviae meningitis: a rare case report and review of the literature - He, Yanlang; Liu, Jia; Wei, Sheng; Chen, Jianyong (Frontiers in Medicine, 2024)
Currently, there is a lack of knowledge about aeromonas caviae meningitis. We report the first case of super-refractory status epilepticus(SRSE) in woman with aeromonas caviae meningitis. Our case reflects that aeromonas caviae meningitis may cause severe SRSE. Effective treatment for epilepsy is crucial for improving the prognosis of similar patients. As suggested in the Concensus protocol for SRSE by Gomes D et al, the combination of up to one anesthetic drug and three non-anesthetic anti-epileptic drugs may be helpful and important in controlling SRSE caused by aeromonas caviae meningitis.